Left thoracotomy for coronary artery bypass grafting after sternoturnover for pectus excavatum: a case report - Mamoru Hamuro; Kenji Yamamoto; Tomoyuki Yamada; Sakae Enomoto (Surgical Case Reports, 2019)
Abstract Background Sternoturnover is a surgical procedure for pectus excavatum. Cardiac surgery in patients with a history of sternoturnover has been rarely reported and is a surgical challenge because it is unknown how median sternotomy or the use of a sternal retractor affects the postoperative stability of the thorax and respiratory function. We report a successful coronary artery bypass grafting through left thoracotomy in a patient treated with sternoturnover for pectus excavatum. Case presentation A 53-year-old man, who underwent sternoturnover in his childhood, was diagnosed with acute myocardial infarction, and percutaneous coronary intervention was performed as the acute treatment of the culprit lesion. Because residual lesions were present, he was referred to our department for coronary artery bypass grafting. Enhanced computed tomography revealed bilateral occlusions of the internal thoracic arteries and a small fragile sternum after fixation. Considering postoperative respiratory dysfunction associated with instability of the thorax following median sternotomy, we selected left thoracotomy for coronary artery bypass grafting. Convalescence was uneventful without any respiratory complications. Conclusion Left thoracotomy is useful for coronary artery bypass grafting in patients previously treated with sternoturnover for pectus excavatum because it can avoid respiratory dysfunction associated with median sternotomy.